Q: What is the expression for the sum of 1 and twice a number n?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

1 - 2n

5 (N + 1)

The algebraic expression for "4 less than the sum of a number and 5" is (n + 5) - 4, where n represents the unknown number.

A number . . . ' x 'Its reciprocal . . . 1/xTwice its reciprocal . . . 2/xThe sum of (the number) and (twice its reciprocal) . . . x + 2/xThe equation:x + 2/x = 3Multiply each side of the equation by 'x' :x2 + 2 = 3xSubtract 3x from each side:x2 - 3x + 2 = 0Factor the left side, in order to see what's going on:(x - 1) (x - 2) = 0This is true if 'x' is either ' 1 ' or ' 2 '.x = 1The sum of the number and twice its reciprocal . . . 1 + 2/1 = 3X = 2The sum of the number and twice its reciprocal . . . 2 + 2/2 = 3

The sum of an odd and an even number is odd. Any odd number can be expressed as 2n + 1 (for some integer "n"). Any even number can be expressed as 2m (for another integer, "m"). The sum of the two is 2(m+n) + 1. Since the expression in parentheses is an integer, multiplying it by 2 gives you an even number. Adding 1 makes the entire expression odd.

Related questions

1 - 2n

5 (N + 1)

1

2x^2 - 1

The algebraic expression for "4 less than the sum of a number and 5" is (n + 5) - 4, where n represents the unknown number.

The units digit of a two digit number exceeds twice the tens digit by 1. Find the number if the sum of its digits is 10.

18. 1+8=9 9x2=18

17x+(1+x)

y = 1/3 (x+7)

A number . . . ' x 'Its reciprocal . . . 1/xTwice its reciprocal . . . 2/xThe sum of (the number) and (twice its reciprocal) . . . x + 2/xThe equation:x + 2/x = 3Multiply each side of the equation by 'x' :x2 + 2 = 3xSubtract 3x from each side:x2 - 3x + 2 = 0Factor the left side, in order to see what's going on:(x - 1) (x - 2) = 0This is true if 'x' is either ' 1 ' or ' 2 '.x = 1The sum of the number and twice its reciprocal . . . 1 + 2/1 = 3X = 2The sum of the number and twice its reciprocal . . . 2 + 2/2 = 3

The sum of an odd and an even number is odd. Any odd number can be expressed as 2n + 1 (for some integer "n"). Any even number can be expressed as 2m (for another integer, "m"). The sum of the two is 2(m+n) + 1. Since the expression in parentheses is an integer, multiplying it by 2 gives you an even number. Adding 1 makes the entire expression odd.

Question is about 5x + x + 6 ie 6 (x + 1)